Of women bonds: motherhood, sisterhood, and the ethics of care in Toni Morrison's "Sula" and "A Mercy" - Natalia Fontes de Oliveira (2011)
In this thesis I analyze Toni Morrisons Sula and A Mercy, concentrating on women bonds. I focus specifically on motherhood and sisterhood as the women characters are constantly affected by such relationships. The present works are discussed in the light of feminist and black feminist theories. I show that in Sula there are different types of mothering, demonstrating that the characters challenge stereotypes usuallyassociated with the black mother. I also argue that mother-daughter bonds are not limited to biological connections, as illustrated by A Mercy. In both novels, motherdaughter bonds greatly affect the women characters subjectivities, even if not always positively. Furthermore, I investigate the intensive sisterhood bonding in Sula and other types of sisterhood in A Mercy. I suggest that sisterhood has many forms and is not limited to bonds among black women. Through these friendships,the characters are able to shape their own subjectivities and struggle forempowerment. However, the alteration of the ethics of care causes many women bonds to rupture as the characters resort to unconventional actions to survive in a patriarchal society marked by a tradition of slavery. Consequently, characters suffer different consequences from the severing of their women bonds. I claim that, because of the changes in the ethics of care, the women characters actions cannot be judged according to essentialist paradigms of good and bad